Utilization of Radioactive Contaminated EAF Dust as Material for Making Paving Block - Supriatno, Supriatno; Martono, Dwi Nowo; Agustina, Haruki (Future Science / FSH-PH Publications, 2023)
Electric arc furnace dust, due to steel fabrication by-products, some of that material has been contaminated with radioactive materials from orphan sources. After calculating the concentration of radionuclide activity, it is known that the material meets the criteria for clearance of application and can be used for other purposes according to the appropriate characteristics. By determining the clearance, EAF dust will be processed through a stabilization/solidification method to be used as a material for making paving blocks. Through elemental analysis of EAF dust using the Micro-XRF method, it is known that sample 1 has a Ca content of 3.9%, CaO is 5.51%, Si is 0.64%, and SiO2 is 1.36%, while sample 2 has Ca content. 4.8%, CaO 6.74% Si 0.63% and SiO2 1.34%. The compressive strength test results based on Indonesian National Standard (SNI) 03-0691-1996 give the results of paving blocks included in quality D with a value of 9.2 MPa which can be used for parks or other purposes. In the calculation of cost savings analysis, determining the clearance for EAF dust can provide cost savings of Rp. 205,562,000 compared to if it had to be managed as radioactive waste. The production cost for one paving block using a mixture of EAF dust is Rp. 2,213.77 or Rp. 97,405.88 for units per m2.